Haida totem pole, Sitka, Alaska, June 1906. - Cobb, John N.
Note from Cobb field notebook: Totem pole, Sitka, Alaska. Note from unidentified source: From Kaigani village of Sukkwan; figures are man with spruce root hat, lake monster, unknown, devilfish and bear.